Interventions in functional epiphora–a systematic review - Evelyn Li Min Tai; Allan Lu Lee; Yee Cheng Kueh; Baharudin Abdullah; Bernard Chang (International Journal of Ophthalmology)
AIM: To review the success rates and complications of interventions for functional epiphora in adults. METHODS: A systematic review of English-language articles from the electronic databases PubMed, SCOPUS, and Google Scholar. The primary outcome was subjective resolution or improvement of epiphora symptoms. Secondary outcomes were treatment-related adverse events. Subjects above 18 years of age who underwent surgical or non-surgical treatment for functional epiphora (exhibited symptoms of epiphora with a patent lacrimal system) were included. Articles were excluded if they were 1) case reports; 2) abstract only studies; 3) published in a language other than English. Data extraction was performed independently by two authors. The Effective Public Health Practice Project checklist was used for quality assessment of the included studies. RESULTS: A total of 762 articles were identified; 28 met the study criteria. Most studies employed silicone tube intubation alone or as an adjuvant procedure to dacryocystorhinostomy (DCR). Other interventions included lacrimal probing, balloon dacryoplasty, lateral tarsal strip and botulinum toxin A. DCR had the highest success rate, as well as the longest mean follow-up time. Complications were minor, transient, and mostly stent-related. CONCLUSION: This updated systematic review on the success rates of interventions for functional epiphora in adults proposes the following management algorithm. Dacryocystography (DCG) should be performed in all patients with functional epiphora. If DCG is abnormal, we advocate DCR. If DCG is normal, proceed with dacryoscintigraphy (DSG). We perform DCR for post-sac delay on DSG and lateral tarsal strip for pre-sac delay. Botulinum toxin A is an off-label, short-term treatment option in those with normal DSG.